Bring it! - Grace, N. B. (Shake it up, 2012)
CeCe Jones and Rocky Blue, best friends, neighbors, and background dancers for the hit television show, "Shake It Up, Chicago," compete in a dance marathon for charity and work with the competitors at the Little Cutie Queen beauty pageant.